Tinjauan Literatur: Adaptasi Visual Batik Sunda dan Karawang dengan Keterkaitan Gambar Mahluk Bernyawa - Suliastuti, Iftika (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2025)
Visual adaptation is an activity aimed at developing historical values and symbolic meanings of cultural identity. Regional aesthetic visual identity is expressed through the development of decorative motifs. The decorative motifs of Sunda batik reflect the cultural values and traditional identity of the Sundanese community through the combination of stylization, abstraction, and formal shapes. Cultural transformation has led to the emergence of